Uses and Gratification of Community Radio: A Case Study of Petra Campus Radio - Halim Adiputra Setiawan; Grace Gerungan; Astri Yogatama (Future Science)
This research focuses on community motives in using communication technology, especially radio. The community refers to the listener of campus radio in a university. Community radio is a radio within the scope of a community of religion, university, government, or else. Finding out what is desired by the listener in community radio, a study is conducted using the uses & gratification theory, specifically testing the theory of gratification sought (motive). Gratification sought is a single variable and divided into 4 indicators: motives for seeking information, motives for interaction, motives for self-identity and motives for entertainment / diversion. Motive theory is used to find out what people's desire and need when listening to the radio. Data is collected by questionnaire and distributes through survey to 100 respondents as member of the community. This is a quantitative descriptive research with a single study case. The results of this study indicates that seeking entertainment / diversion is the main motive of the community in listening the campus radio, follow with information seeking. Respondents agree that radio emerge as an entertainment to provide / arise the spirit while they do assignments / works / activities on campus. The most delightful entertainment is music / songs both of Indonesian / western. Thus, the existence of community radio in campus could become a form of entertainment technology to support and improve of the quality of teaching and learning processes, especially for students who become the majority respondents of this study.